Virtual Assistant - Soofastaei, Ali (IntechOpen, 2021)
An intelligent virtual assistant (IVA) or intelligent personal assistant (IPA) is a software agent that can perform tasks or services for an individual based on commands or questions. Improving the quality of artificial intelligence (AI) learning algorithms increases the application of IVAs in different areas. The capabilities and usage of IVAs are expanding rapidly. IVAs, such as Siri, Alexa, and chatbots, help individuals and companies to make better decisions. They learn from collected historical data, and the quality of their recommendations depends on the size of the database they are using. Modern technology has provided a huge capacity for data collection and storage. This means that the new generation of IVAs can help people much better than the previous one. This book examines the applications of IVAs in different areas and presents a clear vision of how this new technology can be used in current and future activities. Chapters cover such topics as the scientific development of VA technology, generating voices for IVAs, the ethics of using IVAs, and using IVAs in banking and finance.